Identification Sugarcane Clones for Tolerance to Juice Quality Deterioration under Delayed Harvest and Different Time Intervals of Staling - Naidu, N. V.; Sridhar, M.; Sabitha, N.; B., Vajantha; T. M., Hemalatha; Balaji, M. S.; K. R., Tagore (International Journal of Bio-resource and Stress Management, 2024)
A study was under taken during January, 2022–March, 2023 at the Agricultural Research Station, Perumallapalle, Chittoor district, Andhra Pradesh, India to evaluate fifteen sugarcane clones including early and mid-late to identify clones with higher shelf life and tolerance to postharvest deterioration and delayed crop harvests. Juice quality parameters determined at 10th, 11th, 12th and 13thmonths of harvest /age and at different time lag intervals of staling (0, 24, 48, and 72 hours showed a linear increase in cane weight reduction regardless of crop age at harvest and staling periods after harvest. Juice extraction (%) also decreased over staling period and delayed crop harvests. Increase in cane weight loss and reduction in juice extraction was significant with increase in staling period. A progressive increase in brix (%), sucrose, purity and CCS in juice was observed up to 11th in early clones and up to 12th months of crop age in mid-late clones and thereafter decreased. Per cent brix (%) showed a linear trend at all time lag intervals of staling regardless of the clones studied. Brix (%) in juice progressively increased from 0 to 72 hours of staling. Sucrose, purity and CCS per cent declined at 48 hrs in early group and at 72 hrs in mid-late clones after harvest. Reduction in sucrose, purity and CCS was significant with increased staling periods. Among the clones 2003V46 (TC), 2016T 7, COA14328, COA20324, COA19322 and 2009V89 were found to be relatively more tolerant to delayed harvest and post-harvest deterioration compared to the popular standard CO86032 and other test clones studied. All these clones have also recorded higher cane yield and CCS yield at harvest.